Chimera : a Jim Chapel mission - Wellington, David (Wellington, David. Jim Chapels missions., 2013)
Afghanistan veteran Jim Chapel has been enlisted in a new war. This time it's in his own backyard and even more deadly. A small band of fugitives escapes from a secret upstate New York military facility, leaving a trail of bodies in its wake. Each fugitive has a target, an innocent civilian, and will not stop until the target has been eliminated. Chapel, a wounded Special Forces veteran, is tasked with hunting this group of extremely deadly, genetically modified killers and unraveling the mystery behind their existence. But are the killers really rogues, or are they part of a sinister conspiracy that reaches into the highest levels?